Condicionantes institucionais ao investimento em infraestrutura: Elaboraç\~ao, avaliaç\~ao e seleç\~ao de projetos - Rennaly Patricio Sousa; Fabiano Mezadre Pompermayer (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This paper analyzes the effect that shortcomings in the processes of "development, evaluation and selection of project" investments in infrastructure produce on the deployment and operation of these projects. The methodology adopted was to identify best practices in project development, evaluation and selection from literature and national and international experience, public and private, and then compare with the practices adopted in the six case studies listed in the research project of Ipea entitled "Institutional constraints to infrastructure investment". In some cases, it can be observed that when the decision making for the implementation of the project was based on very preliminary studies, without a robust process of evaluation and selection of alternatives and risk identification, the implementation of the project suffered several delays and increases in costs against the expected. In some cases, it was not possible to identify if there was any formal assessment of benefits and costs. Despite the small number of cases studied, this conclusion is confirmed by the project management theory. However, it is noteworthy that a better preparation, evaluation and selection of projects is necessary but not sufficient for success in the implementation of infrastructure projects. It was also possible to identify the high potential impact of uncertainty of issues in environmental, expropriation, local and regional social impacts and contracting of public works on the performance of projects.
Keywords: D61; H43; O220; 330; infrastructure; project analysis